Pr3+ Ion-Substituted Ni-Co Nano-Spinel Ferrites: Their Synthesis, Characterization, and Biocompatibility for Colorectal Cancer and Candidaemia - Suriya Rehman; Balasamy Rabindran Jermy; Irfan A. Rather; Jamal S. M. Sabir; Suhailah S. Aljameel; Munirah A. Almessiere; Yassine Slimani; Firdos A. Khan; Abdulhadi Baykal (MDPI AG, 2023)
Nanotherapeutics have attracted tremendous research interest in the modern pharmaceutical and biomedical industries due to their potential for drug development, targeted delivery, and therapeutic applications. Therefore, the current study underpins the synthesis of praseodymium ion (Pr3+)-substituted Ni0.5Co0.5Fe2O4 nano-spinel ferrites, (Co0.5Ni0.5PrxFe2−xO4 (0.0 ≤ x ≤ 0.10) NSFs, CoNiPr (x ≤ 0.10) NSFs) via the sonochemical route for its application as a nanotherapeutic treatment option. The synthesized nanomaterial was characterized using various analytical techniques, including scanning/transmission electron microscopy (SEM) and X-ray powder diffractometry (XRD). After substitution with Pr (x = 0.08), the particle size, polydispersity index, and zeta potential analysis indicated an increase in hydrodynamic diameter, with an average zeta potential value of −10.2 mV. The investigation of CoNiPr (x ≤ 0.10) NSFs on colorectal cancer (HCT-116) cells demonstrated a significant effect on cancer cell viability. The inhibitory concentration (IC50) of CoNiPr (x ≤ 0.10) NSFs was between 46 ± 0.91 and 288 ± 8.21 for HCT-116 cells. The effect of CoNiPr (x ≤ 0.10) NSFs on normal human embryonic kidney (HEK-293) cells showed a reduction in the HEK-293 cell viability; however, the cell viability was better than HCT-116. The NSFs treatment also showed morphological changes in cancer cell nuclei, as revealed by DAPI (4',6-diamidino-2-phenylindole), nuclear disintegration, and chromatic fragmentation, which are signs of apoptosis or programmed cell death. To examine the potential antifungal effects of CoNiPr NSFs on Candida albicans, known to cause candidemia among cancer patients, the viability of the cells was assessed post treatment with CoNiPr (x ≤ 0.10) NSFs. The increasing ratio of dopant had a moderate impact on the percentage of cell viability loss of 42, 44, and 43% with x = 0.06, 0.08, and 0.10, respectively. These results reinforce that increased dopant significantly impacts the antifungal properties of the synthesized nanomaterial. These findings support the idea that NSFs might be useful in pharmaceuticals.